PD-1 and PD-L1 inhibitors in oesophago-gastric cancers. (28th January 2020) - Akin Telli, Tugba; Bregni, Giacomo; Camera, Silvia; Deleporte, Amelie; Hendlisz, Alain; Sclafani, Francesco
Abstract: Oesophago-gastric cancers (OGCs) are aggressive tumours. While better peri-operative strategies, increased number of cytotoxic agents and availability of targeted therapies have improved survival, there remains an unmet need for novel treatment approaches. Immune checkpoint inhibitors (ICIs) have marked a new era in cancer management with unprecedented results in several malignancies. Although OGC lagged behind other solid tumours, evidence has increasingly accumulated supporting the contention that modulation of the anti-cancer host immune response may be beneficial for at least some patients. Many trials have been completed in Eastern and Western countries, some of these leading to the approval of ICIs in the refractory setting, and favorable opinion from regulatory agencies is expected also in treatment-naïve, advanced OGC. Furthermore, studies are evaluating ICIs in the early stage setting and exploring the potential of combination treatments. In this article we discuss the biological bases underlying the successful development of ICIs in OGC and review the available data on PD-1 and PD-L1 monoclonal antibodies in this disease. Also, we present ongoing clinical trials of these ICIs that could shape the future treatment landscape of OGC. Highlights: Immunotherapy in oesophagogastric cancer is supported by a strong biological rationale. Pembrolizumab and nivolumab are now approved for patients with refractory tumours. Trials are currently testing PD-1/PD-L1 inhibitors in other treatment settings. More approvals of immunotherapy agents are expected in the near future.